Analyzing Digital Marketing in Indonesia Online Transportation Sector: A Social Network, Sentiment, and Topic Analysis - Valentino Aris; Andi Balqis Mutiara Asizah (Fundamental and Applied Management Journal, 2026)
This study aims to evaluate the effectiveness of Grab’s digital marketing strategy in Indonesia’s online transportation sector using a Social Media Network Analysis approach. Data were collected from the social media platform X (formerly Twitter) through web scraping of relevant hashtags and keywords, followed by cleaning to remove irrelevant content. The analysis, conducted using Gephi, examined network structure through metrics such as degree centrality, betweenness centrality, closeness centrality, modularity, and community detection. Results reveal that @grabid is the primary conversation hub with high degree centrality, indicating dominance in information dissemination. The network exhibits two major communities, centered on Grab and Gojek, reflecting narrative competition in the industry. Modularity analysis (score = 0.438) indicates moderately distinct communities, presenting opportunities for targeted marketing. Betweenness centrality findings highlight a small number of strategic connectors, while closeness centrality suggests efficient network connectivity with a small-world property. These insights underscore the potential of SNA to identify key influencers, optimize message dissemination, and strengthen brand positioning. Content analysis revealed that the majority of consumer discussions carried a positive sentiment. The study contributes to digital marketing literature by demonstrating SNA’s utility in mapping brand-related social media interactions and offers practical recommendations for data-driven campaign strategies.